2004
DOI: 10.1128/jcm.42.12.5458-5461.2004
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Schistosomiasis by Reagent Strip Test for Detection of Circulating Cathodic Antigen

Abstract: A newly developed reagent strip assay for the diagnosis of schistosomiasis based on parasite antigen detection in urine of infected individuals was evaluated. The test uses the principle of lateral flow through a nitrocellulose strip of the sample mixed with a colloidal carbon conjugate of a monoclonal antibody specific for Schistosoma circulating cathodic antigen (CCA). The strip assay to diagnose a group of highly infected schoolchildren in Mwanza, Tanzania, demonstrated a high sensitivity and association wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
187
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 224 publications
(194 citation statements)
references
References 11 publications
5
187
2
Order By: Relevance
“…This indicates that levels of serum and urine CCA and CAA decrease significantly some weeks after treatment, constituting a biomarker for schistosomiasis cure. Additional studies have found that detection of CCA and CAA offers some advantages for schistosomiasis diagnosis, such as the identification of active infections and a good diagnostic performance, particularly in highly infected individuals (11) (12) .…”
Section: Introductionmentioning
confidence: 99%
“…This indicates that levels of serum and urine CCA and CAA decrease significantly some weeks after treatment, constituting a biomarker for schistosomiasis cure. Additional studies have found that detection of CCA and CAA offers some advantages for schistosomiasis diagnosis, such as the identification of active infections and a good diagnostic performance, particularly in highly infected individuals (11) (12) .…”
Section: Introductionmentioning
confidence: 99%
“…Because of less field applicability of the ELISA-based method for the diagnosis of schistosomiasis at a community level, reagent strip/dipstick based assay has INTRODUCTION D iagnosis of intestinal schistosomiasis by demonstrating the parasites' eggs in feces using convectional techniques like Kato and formol-ether concentration has been claimed for its low sensitivity in case of low intensity of infection, post-treatment situations as well as for egg output fluctuation (De Vlas & Gryseels, 1992;Gryseels & De Vlas, 1996;Engels et al, 1996;Kongs et al, 2001). Detection of specific antibodies induced against the different stages of the parasite using immunological techniques has been suggested as a solution to minimize the risk of low sensitivity of the parasitological techniques (Rossi et al, been developed for the diagnosis of both intestinal and urinary schistosomiasis by detecting CCA of the parasites in urine of infected individuals regardless of species specificity, according to the information provide by the manufacturer (B.V. European, Veterinary Laboratory, The Netherlands) and Van Dam et al (2004). The test has been found to be highly sensitive and specific in detecting CCA in the urine of Schistosoma mansoni -infected individuals in high endemic areas of the disease (Van Etten et al, 1994;Van Dam et al, 2004;Stothard et al, 2006).…”
mentioning
confidence: 99%
“…Detection of specific antibodies induced against the different stages of the parasite using immunological techniques has been suggested as a solution to minimize the risk of low sensitivity of the parasitological techniques (Rossi et al, been developed for the diagnosis of both intestinal and urinary schistosomiasis by detecting CCA of the parasites in urine of infected individuals regardless of species specificity, according to the information provide by the manufacturer (B.V. European, Veterinary Laboratory, The Netherlands) and Van Dam et al (2004). The test has been found to be highly sensitive and specific in detecting CCA in the urine of Schistosoma mansoni -infected individuals in high endemic areas of the disease (Van Etten et al, 1994;Van Dam et al, 2004;Stothard et al, 2006). On the other hand, the test was found to be valueless in the diagnosis of schistosomiasis haematobium (Stothard et al, 2006).…”
mentioning
confidence: 99%
“…To date, currently available CCA tests have been shown to have moderate to good reliability in detecting S. mansoni 54,[61][62][63][64][65] but poor performance in detecting S. haematobium 61,[66][67][68][69] . Recently, the Bill & Melinda Gates Foundation sponsored evaluation studies on the accuracy of the urine CCA tests for determining schistosomiasis prevalence in young children in African countries.…”
mentioning
confidence: 99%
“…The detection of circulating anodic antigen (CAA) and circulating cathodic antigen (CCA) in serum and urine, using the ELISA 52,53 or dipstick platforms 54 , and antigen capture with monoclonal antibodies 55 have been the most widely studied methods. Their main advantages are high specificity, positive correlation with worm burden, and the possibility for estimation of infection intensity [56][57][58] .…”
mentioning
confidence: 99%